Endoscopic treatment of rectal neuroendocrine tumors: a consecutive analysis of multi-institutional data - Jae Won Shin; Eun-Jung Lee; Sung Sil Park; Kyung Su Han; Chang Gyun Kim; Hee Chul Chang; Won Youn Kim; Eui Chul Jeong; Dong Hyun Choi (Annals of Coloproctology)
Purpose The incidence of rectal neuroendocrine tumors (NETs) is increasing owing to a rise in colonoscopy screening. For the endoscopic removal of NETs, complete resection including the submucosal layer is essential. Therefore, appropriate endoscopic resection techniques are of critical importance. This study aimed to analyze data on rectal NETs and help provide guidance for their endoscopic treatment. Methods A retrospective analysis was conducted on data from patients who underwent resection for rectal NETs at 6 institutions between 2010 and 2021. Results A total of 1,406 tumors were resected from 1,401 patients. During a mean follow-up period of 55.4 months, there were 8 cases (0.5%) of recurrence. Overall, a complete resection was achieved in 77.6% of the patients, with modified endoscopic mucosal resection (mEMR) and endoscopic submucosal dissection (ESD) showing the highest rate at 86.0% and 84.9%, respectively, followed by conventional EMR (cEMR; 68.7%) and snare polypectomy (59.0%). In the subgroup analysis, statistically significant differences were observed in complete resection rates based on tumor size. ESD and mEMR demonstrated significantly higher complete resection rates compared with cEMR. Univariate and multivariate analyses showed that tumor location of the lower rectum and advanced techniques (mEMR and ESD) were significant prognostic factors for complete resection rates. Conclusion When encountering rectal subepithelial lesions on endoscopic examination, endoscopists should consider the possibility of NETs and carefully decide on the endoscopic treatment method. Therefore, it is advisable to perform mEMR or ESD to achieve complete resection, especially for rectal NETs measuring ≤10 mm.